TINJAUAN KELENGKAPAN PENGISIAN ASSESMEN AWAL MEDIS PASIEN PENYAKIT DALAM DI RUMAH SAKIT TK.III DR. REKSODIWIRYO PADANG TAHUN 2021 - Wisandra, Ade; Ilahi, Vitratul; Rahman, Khalilul (Ensiklopedia of Journal, 2022)
Incompleteness in filling out medical record files causes records to become out of sync and patient health information is difficult to identify. The initial medical assessment form is considered complete if the identification, authentication, and recording items are met. Preliminary survey results indicated that 8 out of 10 initial medical assessment forms were incomplete at Reksodiwiryo Hospital in Padang. Thisi studyi aims to review thei completenessi ofi completing thei initiali medicali assessmenti for internal medicine patients at RST Reksodiwiryo on 1-3 July 2024. Thisi researchi isi ai quantitativei studyi withi ai idescriptive iapproach, withi ai population of 3,818 forms of initial assessment and a sample of 97 forms. Data was collected using observation with a checklist table instrument and analyzed using editing, coding, processing and cleaning techniques with iunivariate ianalysis. Thei resultsi showedi thati oif ithe 97 initial medical assessment forms for outpatient internal medicine patients, 14 (14.4%) were incomplete in identification, 50 (51.5%) were incomplete in recording, and 77 (79.4%) were incomplete in authentication. In total, 62 (63.9%) forms were incomplete. It is recommended that medical personnel fill out the initial medical assessment form for outpatients completely and thoroughly in accordance with the hospital's SOP.Keywords: Initial Medical, Assesment Form, Medical Record